Enzymatic Hydrolysis of Cassava Starch Using Barley Malt Amylases - da Luz, Felipe Staciaki; Bueno, Adrielle Ferreira; Caetano, Renata Nascimento; Rodrigues, Paulo Rogério Pinto; Banczek, Everson do Prado (Orbital: The Electronic Journal of Chemistry, 2021)
Barley malt was used as a source of amylases for the hydrolysis of cassava starch to produce reducing sugars for the alcoholic fermentation. Two routes of hydrolysis were evaluated in this work. One using milled barley malt and the other using the enzyme extract of this grain. The first one evaluated three concentrations of milled barley malt: 5, 10 and 15% (w/w) and there was no significant difference between the values of reducing sugars obtained as a function of the three concentrations. Three concentrations were also tested for barley malt extract: 0.5, 1.0 and 1.5 mL of extract. The higher content of reducing sugars was found for the 0.5 mL concentration of extract. The barley malt extract was more efficient in the enzymatic hydrolysis of cassava starch due to a better contact of the enzymes with substrate. The alcoholic fermentation of the wort obtained with 0.5 mL yielded an ethanol content of 7.74 ± 3.19 g/L with an efficiency of 88.6%.DOI: http://dx.doi.org/10.17807/orbital.v13i3.1525